Empowering Housewives Through Banana Nugget Processing Innovation as an Effort to Improve the Economy in the Central Ende District: Pemberdayaan Ibu Rumah Tangga Melalui Inovasi Pengolahan Nugget Pisang Sebagai Upaya Peningkatan Ekonomi Di Kecamatan Ende Tengah - Maria Endang Jamu; Santy Permata Sari Sari (CONSEN: Indonesian Journal of Community Services and Engagement, 2023)
Bananas are one of the local potentials that have not been utilized optimally by housewives in Potu District. The participants in this community service activity are housewives. Housewives were chosen as the object in this activity, because housewives have a very large role in household life. Housewives are required to help increase family income, and one way is to create innovations that have economic value. Bananas are one of the staple foods that are easy to obtain in Potu sub- district, almost all of the people have land and grow bananas. Bananas, which until now have only been boiled and fried, can be turned into valuable products, one of which is making nuggets using banana as the basic ingredient. Banana nuggets can then be sold around existing complexes or kiosks, thereby increasing income.